Risk factors of post-ERCP pancreatitis in high-risk patients despite prevention with prophylactic pancreatic stents. (2nd January 2020) - Dubravcsik, Zsolt; Hritz, István; Szepes, Attila; Madácsy, László
Abstract: Objectives: To analyze risk factors of post-ERCP pancreatitis (PEP) in high risk patients in whom prophylactic pancreatic stents (PPSs) were intended to use to prevent endoscopic retrograde cholangiography (ERCP)-related complications. Patients and methods: Three hundred and seventeen high-risk patients for developing PEP were considered for preventive pancreatic stent placement in our endoscopy unit over 5 years. 5 Fr, 3–5 cm long PPSs were used. All data were collected in a predefined database. Development of PEP despite PPS placement was analyzed. Results: PEP occurred in 29 of 288 successfully stented patients (10.07%; 24 mild, four moderate, one severe). PPS was protective against all risks factors except for sphincter of Oddi dysfunction (SOD). PPS related complication rate was 2.78% ( n  = 8). Unsuccessful stenting occurred in 29 patients (9.15%), PEP developed in 41.38% ( n  = 12; seven mild, four moderate, one severe). Those patients who had more patient related risk factors were more likely to develop PEP despite preventive measures with PPS. On the contrary, PPS placement was less successful in patients who had more procedure related risk factors. Conclusions: PPS is protective against all risks factors of PEP except for SOD in high-risk patients. More vulnerable patients who have more patient-related risk factors are more likely to develop PEP despite PPS is used, while more complex procedures predispose to unsuccessful PPS placement in patients with more procedure-related risk factors. PPS insertion in high-risk patients is effective and safe preventive method and the procedure related complication rate is reasonably low.